The Omission of Verbs in Coordinate Ellipsis and Confusion Caused by Coordinate Structures - Linh, Nguyen Thuy (Journal of Letters, 2018)
The concept of ellipsis is a controversial and much discussed subject within the field of linguistics. Ellipsis is a term that is used to describe the omission of words or phrases in a sentence. However, this kind of omission can lead to misunderstanding and confusion. This paper will focus on one particular type of ellipsis: ellipsis in coordinate structures, in which the similar constituents have been left out. The main aim of this study is to investigate the confusion caused by elided verbs in coordinate elliptical constructions, and provides an opportunity to enhance our understanding of this linguistic phenomenon. Data for this study was collected using an online-survey, for which the respondents were native speakers of German.